DESIGN THINKING APPROACH IN TRANSLATING BANYUMAS TOURISM TEXTS - Nadia Gitya Yulianita; Nisa Roiyasa; Tri Wahyu Setiawan Prasetyoningsih (Universitas Islam Sumatera Utara (UISU), 2020)
The research aims to identify the students’ translation quality in translating Banyumas tourism texts. Moreover, this research tries to find out the effect of design thinking approach in translation class. This research was conducted by applying descriptive qualitative method. In other words, this research describes the effect of design thinking approach to the students’ translation by dividing students of English Diploma Study Program, Universitas Jenderal Soedirman enrolling on Translation Indonesian-English class into two classes. Class A uses design thinking approach in translating the texts, while class B does not. The students focus on translating Banyumas tourism texts. After the students translate the texts, the researchers and raters do a focus group discussion to check and rate their translation quality in terms of accuracy. The result shows that the translation quality of class A is better than that of class B. It can be seen from the accuracy point of class A which is 2.95 meanwhile, class B has 2.90 for its accuracy. This proves that design thinking approach is suitable to teach translation.